Retención de microplásticos en tuberías de agua potable que contienen incrustaciones calcáreas en Riobamba - Córdova Villagrán, Ángel André (2024)
Microplastics are currently being studied for causing toxic and mechanical effects, resulting in behavioral changes and genetic alteration. Globally, an estimated 24.4 billion microplastics are in the upper layers of the world's oceans. In Riobamba, through studies generated in 2018, the analysis results indicated a 19% presence of microplastics in the water. However, there is no current data on the amount of microplastics, so it was necessary to identify that in the present study through exploration and analytical methodology. The influence of calcareous incrustations on the retention of microplastic particles in drinking water pipes was analyzed. For the identification of microplastics in drinking water, the methodology of Microplastics in Riobamba's drinking water was applied, which was based on the UNACH experimentation of fluorescence of inert materials through vacuum filtration of water samples with a cellulose filter and pink Bengal dye. Subsequently, they were observed in a stereoscope, obtaining the identification of microplastics in 9 potable water distribution networks in the city of Riobamba. Eighteen samples were taken, 2 for each distribution network. The results of the analysis show that all the drinking water samples of Riobamba present microplastics; the Piscin network is the one that registers the highest concentration of these particles, while the Yaruquíes network presents the lowest. Microplastics in the water could represent a risk to human health. It is important to note that Riobamba's water has "hard water" characteristics; its distribution network pipes have calcareous incrustations, which retain and delay the degradation of microplastic particles. Being a total percentage of the presence of these particles, it is left as a precedent for future research to analyze the incidence of these particles on the consumer's health.